الآثار المترتبة على انتهاء الأعمال العدائية بين قانون النزاعات المسلحة وقانون اللجوء إلى استخدام القوة المسلحة - الرتمي, عبد الحفيظ (University of Eloued جامعة الوادي, 2021)
تُخَلِفَ الحروب والنزاعات المسلحة آثارا مادية وشخصية؛ يتطلب من المجتمع الدولي مواجهتها واتخاذ التدابير في شأنها؛ ومنها الآثار المترتبة على انتهاء الأعمال العدائية، والتي قد يسبقها وقف إطلاق النار أو إبرام اتفاق الهدنة بين الأطراف المتنازعة، بغرض وضع الترتيبات اللازمة لتسوية القضايا العالقة، يتعين في حالة الاحتلال على المحتل سحب قواته من هذا الإقليم، وفي حالة الحصار رفعه، وإلى ضرورة وضع الترتيبات اللازمة لإزالة الألغام، وإعادة الأسرى إلى أوطانهم، وإحالة مرتكبي الانتهاكات الجسيمة إلى المحكمة الوطنية أو المحكمة الجنائية الدولية، بغرض جبر ضرر الضحايا ومعاقبة المجرمين أو العفو عنهم، والتوجه إلى إرساء بناء السلام وعودة العلاقات الدبلوماسية إلى أول عهدها. Abstract: the war and armed conflicts often cause many material and personal serious consequences that the international society should confront and take necessary measures about them .Among these consequences , those resulting of the end of hostilities, probably preceded by a ceasefire or by a truce agreement between the conflicting parties, aiming to set the necessary arrangements to settle the pending issues. In case of occupation, the occupying power is obliged to withdraw its forces from this territory, lift the embargo, set the necessary arrangements for demining, to return the prisoners to their homelands; to refer the perpetrators of grave violations before the National justice or the International Criminal Court, in the purpose of repairing the victims and punishing the criminals or pardoning them; aiming to lay the peace and return the diplomatic relationship to its first era.
The Consequences Resulting from the end of Hostilities between the Law of Armed Conflicts and the Principles of Armed Forces Use
مقال
Keywords: الآثار ; الأعمال، ; العدائية ; الدولي ; السلام; Consequences ; hostilities ; international, peace ; relationship